Flavonoid Fraction of Orange and Bergamot Juices Protect Human Lung Epithelial Cells from Hydrogen Peroxide-Induced Oxidative Stress. (21st June 2015) - Ferlazzo, Nadia; Visalli, Giuseppa; Smeriglio, Antonella; Cirmi, Santa; Lombardo, Giovanni Enrico; Campiglia, Pietro; Di Pietro, Angela; Navarra, Michele
Abstract : It has been reported that oxidant/antioxidant imbalance triggers cell damage that in turn causes a number of lung diseases. Flavonoids are known for their health benefits, and Citrus fruits juices are one of the main food sources of these secondary plant metabolites. The present study was designed to evaluate the effect of the flavonoid fraction of bergamot and orange juices, on H2 O2 -induced oxidative stress in human lung epithelial A549 cells. First we tested the antioxidant properties of both extracts in cell-free experimental models and then we assayed their capability to prevent the cytotoxic effects induced by H2 O2 . Our results demonstrated that both Citrus juice extracts reduce the generation of reactive oxygen species and membrane lipid peroxidation, improve mitochondrial functionality, and prevent DNA-oxidative damage in A549 cells incubated with H2 O2 . Our data indicate that the mix of flavonoids present in both bergamot and orange juices may be of use in preventing oxidative cell injury and pave the way for further research into a novel healthy approach to avoid lung disorders.